Parameters and Petrographic Interpretation of In Situ Copper Leaching - William J. Mallio (The Minerals, Metals and Materials Society, 1981)
Substantial differences between in situ and conventional technology require that in situ ore grade be established for deposit as distinct from the total contained metal value. Establishing an in situ ore grade involves determining the fraction' of the contained metal that can be leached by the fluid. This depends on the proportion of the ore minerals that occur on fluid flow paths as defined by the permeability distribution. Mechanisms involved in the in situ mining of sulfides are: oxidation of the sulfur, solution of the metals, complexing of the released metals, and a transport to a recovery point. Metal ions may be delayed or lost due to inefficiencies in these pro-cess steps or by reactions of the metal ions in solution with the rock. These reactions can involve precipitation of new phases, exchange of the metals of the interest with Ca or Na in clays or zeolites, retention of metals in oxidized mineral grains, or secondary enrichment of other sulfides along the paths of the solution flow. The efficiency of solution of metals and potential loss or delay mechanisms are controlled by local equilibria (the Eh, pH conditions) present in different parts of the ore zone. Permeability distribution in the rock mass and the coincidence of ore minerais with flow channels must be determined before a deposit can be judged suitable for in situ mining. Laboratory studies indicate that the natural permeability system is dependent on the degree of cementation of veins by late generation hydrothermal activities. The major conclusions of the study are:, 1. Deposit selection is critical; suitable deposit types include deep lying sedimentary deposits, selected zones of porphyry systems and vein controlled hydrothermal deposits; 2. Adequate laboratory and geochemical analyses should be undertaken through quantitative petrographic study and permeability mapping; and 3. Economic incentives for in situ mining must consider limitations of recovery caused by inefficiencies in dissolution and transport associated with particular deposits.